The Analysis of Inflation Effect, Interest Rate and Exchange Rate on Financing: Third-Party Funds as an Intervening Variable of Sharia Banking in Indonesia - Anton Bawono; Ulinnuha Ulinnuha; Muhammad Kava Nasikin (al-Uqud : Journal of Islamic Economics, 2021)
The purpose of this study was to determine the effect of inflation, interest rate and the exchange rate on financing, with third-party funds sharia banking as an intervening variable in Indonesia. This research uses quantitative research using path analysis as data analysis. The data of this study uses secondary data with the time series method which includes of total financing, mudharabah financing, musyarakah financing, murabahah financing, third-party funds, inflation, interest rates, exchange rate. The data have been obtained and analyzed using Eviews software tool version 6.The results of this study indicate that inflation, interest rates have not effect on total financing, mudharabah financing, musyarakah financing and murabahah financing. Exchange rate have a negativ and significant effect on musyarakah financing and have a positiv and significant effect on murabahah financing. Third-party funds have a positive and significant effect on total of financing, mudharabah financing, musyarakah financing and murabahah financing. The results of path analysis show that Third-Party funds cannot mediate the effect of inflation, interest rates and exchange rates the total financing, mudharabah financing, musyarakah financing and murabahah financing.